2020
DOI: 10.1590/0004-282x20190139
|View full text |Cite|
|
Sign up to set email alerts
|

Brainstem auditory pathway of children with acute lymphoid leukemia on chemotherapy with methotrexate

Abstract: Objective: Investigate the auditory pathway in the brainstem of children with acute lymphoblastic leukemia submitted to chemotherapy (by intravenous or intrathecal infusion). Methods: Fourteen children aged between 2 and 12 years with diagnosis of acute lymphoid leukemia were evaluated. The following procedures were used: meatoscopy, acoustic immitance measurements, tonal audiometry, vocal audiometry, transient otoacoustic emissions, and auditory brainstem response. Results: From the 14 children with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
2
3
0
2
Order By: Relevance
“…It is known that this CNS-directed therapy increases the risk of neurologic toxicities, 34 and a small study reported an association between intrathecal methotrexate and auditory pathway impairment in the brainstem. 35 Furthermore, fluid overload and infections are important complications during ALL treatment, for which respectively diuretics and antibiotics are often applied. Many of these agents are potentially ototoxic, including aminoglycosides (eg, gentamicin, tobramycin), loop diuretics (eg, furosemide), and glycopeptides (eg, vancomycin).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that this CNS-directed therapy increases the risk of neurologic toxicities, 34 and a small study reported an association between intrathecal methotrexate and auditory pathway impairment in the brainstem. 35 Furthermore, fluid overload and infections are important complications during ALL treatment, for which respectively diuretics and antibiotics are often applied. Many of these agents are potentially ototoxic, including aminoglycosides (eg, gentamicin, tobramycin), loop diuretics (eg, furosemide), and glycopeptides (eg, vancomycin).…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the ribbon synapses hinders transmission of sound and conduction to the brain (where it is interpreted as sound), thereby increasing the hearing thresholds, and causing hearing loss. In addition, MTX treatment impairs both the central and peripheral nervous systems, with the potential for neurotoxicity in the central auditory nervous system [ 7 ]. Our results showed a decline in the number of synaptic ribbons of IHCs in the MTX-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the brainstem auditory system in children (2–12 years) with acute lymphoid leukemia who received MTX treatment, 60% of individuals aged 5 years or less showed an auditory deficit [ 7 ]. The brainstem auditory-evoked potential assessment, used to evaluate ototoxicity in patients undergoing chemotherapy, revealed that 80% of those tested exhibited some form of change and latency delay, with auditory impairment in the lower brainstem being the most common.…”
Section: Introductionmentioning
confidence: 99%
“…[24] meme kanser modeli oluşturulmuş farelere akut MTX uygulamasının zihinsel depresyon ve hafıza kayıplarına neden olduğunu göstermiş ve bu durumu hipokampustaki nörogenezin inhibisyonu ve proinflamatuar enzimlerin artışı ile ilişkilendirmiştir. MTX'in beyin dokusundaki toksisitesinin yeri ve derecesinin belirlenmesi zordur ve manyetik rezonans görüntüleme, elektroensefalografi ve nöropsikolojik testler gibi yardımcı testlerin sonuçları ile klinik belirtiler arasında net bir ilişki gösterilememiştir [6].…”
Section: Biyokimyasal Bulgularunclassified
“…MTX uygulaması, gastrointestinal toksisite, hepatik toksisite, nefrotoksisite, hematolojik toksisite ve nörotoksisite gibi bir çok doku ve organla ilişkili ciddi toksik etkiler ile ilişkilendirilmektedir [5]. MTX'in neden olduğu nörotoksisite, akut, subakut veya geç formda meydana gelebilir ve gerek intratekal ve gerekse intravenöz uygulamadan sonra gözlemlenebilir [6].…”
unclassified